Pentosan polysulfate maculopathy: Keep an eye out for this masquerader (Canadian Eye Care Today, 2022)
Pentosan polysulfate sodium (PPS) (Elmiron; Janssen Pharmaceuticals), a drug used to treat bladder pain and discomfort associated with interstitial cystitis (IC), has been linked to a distinctive vision-threatening maculopathy. As with the case of hydroxychloroquine maculopathy, it is worthwhile for the general ophthalmologist to be familiar with this potentially preventable condition. In this article, we briefly summarize the evidence supporting this association, review the clinical manifestations of PPS maculopathy, and provide some guidance regarding screening protocols.